MiR-133a-5p Facilitates Cuproptosis in Hepatocellular Carcinoma Through Targeting of ATP7B - Ren Q; Zhu X; Wang N; Yu K; Lv W; Wang L; Zang Y; Ma D; Zhou X; Yao J; Shen M; Yu L; et al. (Journal of Inflammation Research, 2025)
Qiaohui Ren,1 Xinyue Zhu,1 Nannan Wang,1 Kang Yu,1 Wei Lv,1 Lianzi Wang,1 Yan Zang,1 Dongyue Ma,1 Xinyi Zhou,1 Junxiao Yao,1 Mengjiao Shen,1 Li Yu,2 Tao Li1 1Department of Clinical Laboratory, The First Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China; 2Anhui Province Key Laboratory of Zoonoses, Anhui Medical University, Hefei, People’s Republic of ChinaCorrespondence: Tao Li, Department of Clinical Laboratory, The First Affiliated Hospital of Anhui Medical University, Hefei, 230032, People’s Republic of China, Email taoli@ahmu.edu.cn Li Yu, Anhui Province Key Laboratory of Zoonoses, Anhui Medical University, Hefei, 230032, People’s Republic of China, Email lilyyu33@126.comPurpose: We explored the effects of miR-133a-5p and ATP7B on cuproptosis in hepatocellular carcinoma.Methods: Initially, we assessed the impact of miR-133a-5p on hepatocellular carcinoma (HCC) using CCK-8 assays, cell scratch assays, and flow cytometry. Subsequently, we utilized elesclomol in combination with copper ions to induce cuproptosis in the HCC cell lines PLC/PRF/5 and Huh-7. We evaluated the influence of miR-133a-5p on cuproptosis using CCK-8 assays, cell scratch assays, flow cytometry, and Western blotting. To elucidate the underlying mechanisms, we employed bioinformatics to identify potential downstream target genes of miR-133a-5p and conducted dual-luciferase reporter assays to confirm the binding sites. Finally, we validated the regulatory effect of miR-133a-5p on ATP7B by modulating miR-133a-5p expression through cell transfection experiments.Results: The results from the CCK-8 assay, cell scratch assay, and flow cytometry demonstrated that miR-133a-5p significantly inhibits the proliferation and migration of HCC cells while promoting their apoptosis. Furthermore, Elesclomol in combination with copper ions induces cuproptosis in HCC cells. Compared to the cuproptosis observed in HCC as a control, miR-133a-5p further suppresses the proliferation and migration of HCC cells, enhances their death, and increases the expression of cuproptosis-related proteins more prominently. Bioinformatics analysis suggested that ATP7B might be a downstream target gene of miR-133a-5p. This was confirmed by dual luciferase assays, which identified a binding site between miR-133a-5p and ATP7B. Additionally, the expression levels of ATP7B were found to decrease or increase in response to the regulation by miR-133a-5p.Conclusion: MiR-133a-5p facilitates cuproptosis in hepatocellular carcinoma through targeting of ATP7B. Keywords: cuproptosis, microRNA, ATP7B, hepatocellular carcinoma